NbMoTaW refractory high entropy alloy composites strengthened by in-situ metal-non-metal compounds - Roh, Aeran; Kim, Daeyoung; Nam, Seungjin; Kim, Dong-Ik; Kim, Han-Yeol; Lee, Kee-Ahn; Choi, Hyunjoo; Kim, Jae-Hun (ELSEVIER SCIENCE SA, 2020)
In this study, a new class of NbMoTaW refractory high-entropy alloys (RHEAs), containing metal-nonmetal compounds, was produced by a power metallurgical route. A non-equilibrium beta Ta phase was generated, while Nb, Mo, Ta, and W formed HEAs during mechanical milling. Additionally, the beta Ta phase attracted oxygen and carbon to form face-centered cubic (FCC) structured metal-non-metal compounds during sintering. The compounds acted as an effective reinforcement to strengthen the RHEAs at both room and high temperatures. Thus, the alloys exhibited superior hardness at room temperature, ranging from 689.46 to 892.38 HV, and excellent compression strength of 1,630 MPa at 800 degrees C. Hence, the alloys are suitable candidates for high-temperature structural materials used in turbine blades and thermal protection sheets. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: MECHANICAL-PROPERTIES; MICROSTRUCTURE; TI; BEHAVIOR; FILMS